THE DESIGN OF INFORMATION SYSTEMS FILING OUTPATIENT MEDICAL RECORDS - Dewi Listiawati Astuti; Hafsah Ghina Ghaida Gunawan; Irda Sari; Rina Kurniawati; Neneng Yuniarty (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: The system information section filing in UPT Puskesmas Rahayu to submit a medical record file to any of the poly, assembling medical records, store medical records, retention medical records are already inactive. This research aims to design and create a system of information filing outpatient medical records in UPT Puskesmas Rahayu in terms of borrowing and return the medical record file as well as facilitate the retention of medical records with the use of qualitative methods. The Data used in the study in UPT Puskesmas Rahayu, namely interviews, observation, and FGD (Focus Group Discussion). This study shows the input data of the patients is in accordance with UPT Puskesmas Rahayu. Input patient data include No RM, the Name of the KK, the Patient's Name, Gender, Address, and Villages. This research resulted in the information system of medical record filing outpatient procedures that can facilitate the officer in the management of the filing of medical records.            Keywords: borrowing and return; medical record filing; puskesmas Abstrak: Sistem informasi bagian filing di UPT Puskesmas Rahayu untuk mengirimkan berkas rekam medis ke setiap poli, assembling rekam medis, menyimpan rekam medis, meretensi rekam medis yang sudah in aktif. Penelitian ini bertujuan untuk merancang dan membuat sistem informasi filing rekam medis rawat jalan di UPT Puskesmas Rahayu dalam hal peminjaman dan pengembalian berkas rekam medis serta mempermudah dalam retensi rekam medis dengan menggunakan metode kualitatif. Data yang digunakan dalam penelitian di UPT Puskesmas Rahayu yaitu wawancara, observasi dan FGD (Focus Group Discussion). Penelitian ini menunjukkan input data pasien sudah sesuai dengan yang ada di UPT Puskesmas Rahayu. Input data pasien meliputi No RM, Nama KK, Nama Pasien, Jenis Kelamin, Alamat, dan Kelurahan. Penelitian ini menghasilkan sistem informasi rekam medis filing rawat jalan yang dapat mempermudah petugas dalam pengelolaan filing rekam medis. Kata kunci: peminjaman dan pengembalian; puskesmas; rekam medis filing